Carbon-based materials for water treatment: adsorption and capacitive deionization studies - Freire, Jessica Miranda Abreu (2023)
In this thesis, the effectiveness of carbon-based materials for water treatment was studied through the examination of adsorption and capacitive deionization technologies. For this purpose, silanized magnetic graphene oxide (MAG-GO1-NH2) was used for toxic metal adsorption and activated carbon (AC) supported on graphite felt (GF) was utilized for water desalination via capacitive deionization (CDI). The first study focused on modifying composites of magnetite and graphene oxide (MAG-GOx) with amino groups (MAG-GO1-NH2) to improve chromium selectivity in a multielement solution containing cadmium and copper ions. Characterization techniques such as Fourier transform infrared, Mössbauer spectroscopy, and X-ray photoelectron spectroscopy confirmed the success of the synthesis and evidenced the presence of nitrogen and oxygen-based moieties able to promote metal adsorption. Adsorption studies showed improved Cr(VI) uptake in the silanized composites compared to the unmodified ones: MAG-GO1-NH2 adsorbed Cr(VI) at 39.0 and 6.5 times more than Cd(II) and Cu(II), respectively, while MAG-GO1 adsorbed Cr(VI) 5 times more than Cd(II) and Cu(II). This enhancement is likely due to hard-hard and electrostatic interactions between Cr(VI) and ‒NH3+ groups that improve adsorption of chromium negative species. The stability of the amino-grafted material was confirmed through reuse experiments, which demonstrated that it could adsorb approximately 100% of Cr(VI) in a multielement solution containing 0.1 mmol L-1 of each ion over 5 cycles. In the second study, simple strategies were studied to enhance the performance of GF-AC electrodes in capacitive deionization (CDI) by modifying electrode thickness (2.0, 3.0, and 5.0 mm), AC mass loading (32, 37 e 55 mg of AC per cm2), and its distribution over GF. Electrochemical characterizations revealed that reducing electrode thickness and increasing mass loading resulted in improved total capacitance (F) and specific capacitance (F gAC−1), resulting in higher salt adsorption capacity (SAC) (from 2,7 mg g‒1 to 7,9 mg g‒1) and salt concentration reduction (Δc) (from 60,8 mg L‒1 to 95,3 mg L‒1) in desalination experiments. Electrodes with a more homogeneous dispersion of AC produced significant enhancements in terms of average salt adsorption rate (ASAR, 45%) and water productivity (P, 59%). These progresses on optimizing the preparation of GF composite materials have paved the way for improving the electrochemical separation of ions and a more practical approach to CDI studies using GF-based electrodes.